A census-based housing vulnerability index for typhoon hazards in the Philippines. (January 2022) - Healey, Sarah; Lloyd, Sophie; Gray, Jasmine; Opdyke, Aaron
Abstract: The Sendai Framework for Disaster Risk Reduction recognises housing as an important element of vulnerability, however, there remains limited understanding of how sub-national housing vulnerability varies spatially. This research sought to develop a municipal-level housing vulnerability index for typhoon hazards, applied at a national scale in the Philippines. We first selected 25 housing vulnerability indicators from the 2015 Philippines census, which were reduced into seven underlying dimensions of typhoon-related housing vulnerability using principal component analysis: housing density, housing quality, crowdedness, tenure security, extreme substandard housing, drinking water source, and structural integrity. These components were then aggregated to create a relative housing vulnerability index. We applied spatial clustering analysis to test for patterns, finding increasing housing vulnerability from north to south, with nuance in municipalities that defy these national trends. Our results offer a more granular view of housing vulnerability which may assist in unpacking how localised housing conditions contribute to disaster risk and assist researchers and government agencies in targeting disaster interventions. Highlights: Identifies 7 dimensions of housing vulnerability using Principal Component Analysis. Develops housing vulnerability index at municipal level in the Philippines. Identifies spatial clustering patterns of housing vulnerability in the Philippines.